Pengaruh partisipasi penyusunan anggaran terhadap kinerja Pemerintah Daerah dengan komitmen organisasi dan gaya kepemimpinan sebagai variabel moderating (studi empiris pada Kota Pekanbaru) - Sisca Mutiara Sari; Kirmizi '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze whether participation budget significantly affect local government performance, but it also aims to determine organizational commitment and leadership style can affect the relationship between budgetary participation on local government performance.  To collect data of this study, survey questionnaires are used. From 100 questionnaires were given to managers in a public sector organization, questionnaires with complete answers were 80 questionnaires. Testing in this study using SPSS software version 17 for windows.  The analysis results indicate that budgetary participation and local government performance have positive relationship and statistically significant. But organization commitment did not indirectly affect local government performance in budgetary participation. Leadership style directly affects local government performance in budgetary participation. Keywords: Participation budgeting, local government performance, organizational commitment, leadership style.